A study into the awareness of Hepatitis C in relation to self protection among the international South Asian students at Uiversity of Bedfordshire in the UK - Dhakal, Chamesh Raj (University of Bedfordshire, UK, 2010)
Hepatitis C virus is one of the major burdens of liver disease in globally. Around 3 percent (170 million) of the world's people has been infected with Hepatitis C virus. The prevalence of Hepatitis C virus infection is below 3 percent, of most countries. In some countries in Africa and South Asia, the prevalence rate is higher up to 15 percent. This study is focus on the awareness of Hepatitis C in relation to self protection among the international South Asian students at University of Bedfordshire in the UK. A quantitative research method based on the close ended questionnaires related to awareness levels of HCV and their self protection strategies is carried out in this study. Literature is accessed by search database, published, unpublished literatures, and Journal paper is used for the review. Data is analysed based on the tabulations, bar diagram and pie chart by using the Excel and SPSS software program. Descriptive analysis is prepared to evaluate the self protection of awareness levels of HVC in South Asian students, who are currently studying in University of Bedfordshire. The survey of study is mainly concerns in the general knowledge and awareness levels of Hepatitis C infection and their self protection. The questions test, the level of knowledge and concern about the infection, awareness about the transmission, treatment of the infection, and where international South Asian students are most likely to get information about Hepatitis C virus infections.